Testing albendazole resistance in Fasciola hepatica: validation of an egg hatch test with isolates from South America and the United Kingdom. Issue 3 (19th March 2013) - Canevari, J.; Ceballos, L.; Sanabria, R.; Romero, J.; Olaechea, F.; Ortiz, P.; Cabrera, M.; Gayo, V.; Fairweather, I.; Lanusse, C.; Alvarez, L.
Abstract: The main goal of the current work was to develop and validate an in vitro fluke egg hatch test, as a method for the detection of albendazole (ABZ) resistance in the liver fluke, Fasciola hepatica . Fluke eggs (200/ml, n = 5) from six different isolates were used in the current experimental work. They were obtained from different geographical locations and named Cullompton (UK), CEDIVE (Chascomus, Argentina), INTA-Bariloche (Bariloche, Argentina), Rubino (Uruguay), Cajamarca (Perú) and Río Chico (Catamarca, Argentina). The fluke eggs were incubated (25°C) for a 12-h period in the presence of either ABZ or its sulphoxide metabolite (ABZ.SO) (5, 0.5 or 0.05 nmol/ml). Untreated eggs were incubated as a control. Incubated eggs (with or without drug present) were kept in darkness at 25°C for 15 days. Afterwards, the trematode eggs were exposed to daylight over a 2-h period. Hatched and unhatched eggs were evaluated using an optical microscope, and the ovicidal activity was assessed for each fluke isolate. A very low ovicidal activity ( ≤ 13.4%) was observed in the ABZ-resistant CEDIVE isolate for both ABZ and ABZ.SO. Conversely, in the INTA-Bariloche and Río Chico isolates, which are suspected to be susceptible to ABZ, ovicidal activities ≥ 70.3% were observed after incubation with ABZ at the lowest concentration tested (0.05 nmol/ml). This finding correlates with that previously described for the ABZ-susceptible Cullompton. Finally, the Cajamarca and Rubino isolates behaved as ABZ resistant, since no ovicidal activity was observed after eggs were incubated with ABZ at 0.5 nmol/ml. Considering the specific results obtained for each isolate under assessment, the egg hatch test described here may be a suitable method for detection of ABZ resistance in F. hepatica .